Effect of Petit-High Pressure Sterilization for Fruit Juice Investigation for Long Time Treatment with Petit-High Pressure Carbon Dioxide Gas - Obuchi, Kaoru; Iwahashi, Hitoshi; Harada, Nobuyoshi; Tamura, Katsuiro (High Pressure Bioscience and Biotechnology, 2008)
Effect of Petit-high pressure carbon dioxide treatment was investigated for microorganisms in Lyceum Barbarum Fruit Juice harvested from China. The Juice was treated with carbon dioxide gas from mild to high pressure (from 3atm to 50atm) conditions, for 1day to 14 days. Colony Favoring Unit on Petri Dishs of LB, YPD, PDF agar medium were decreased to less than 10 in 50atm-1day condition, even in 3atm-14days condition. Surprisingly, similar effect was observed between Petit-high pressure long time treatment (3atm-14days) and high-pressure short time treatment (50atm-1day). The pressure level on food distribution was restricted to be under 4atm. This data shows the possibility and reality of food distribution with mild-pressure carbon dioxide gas on the condition under 4atm.